Sexual compatibility of two cacao genotypes (Theobroma cacao L.) in Santander, Colombia - Coronado-Aleans, Verónica; Arguello-Carreño, Edinson Fernando; Morales-Gómez, Jaiver Enrique (Revista de Ciencias Agrícolas, 2025)
In the context of current research on sexual compatibility in cacao genotypes, previous studies have evaluated self-compatibility and intercompatibility in various materials, including genotypes FSV 1 and ICS 60. However, there remains a need to further characterize these reproductive interactions under specific local conditions, such as those found in the municipality of San Vicente de Chucurí (Santander, Colombia). The objective of this study was to evaluate the genetic compatibility of two cacao genotypes through assisted pollinations and to morphologically characterize the fruits resulting from directed pollinations involving the ICS 60 and FSV 1 genotypes. Field trials were conducted in San Vicente de Chucurí, Colombia, to assess variables associated with fertilization percentage, number of pollinated flowers, and number of unfertilized flowers.. The results revealed significant differences in the sexual compatibility response of the FSV 1 and ICS 60 genotypes. FSV 1 showed 60% self-compatibility and 60% intercompatibility, both as a pollen donor and receptor. In contrast, ICS 60 exhibited a low self-compatibility percentage (11%) and 60% intercompatibility when acting as a pollen donor. In conclusion, these results indicate that both genotypes can be effectively used in polyclonal systems, as they perform well as pollen receptors in intercompatible crosses. This study provides valuable insights for the planning, management, and efficient establishment of these materials in cacao production and breeding programs.